Pengaruh Kinerja Keuangan, Tata Kelola Perusahaan dan Agresivitas Pajak terhadap Pengungkapan CSR - Ersyafdi, Ilham Ramadhan; Irianti, Putri Widya Dwi (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
The purpose of this study was to examine the effect of financial factor including company size, solvency, profitability and corporate governance, namely managerial ownership, institutional ownership, audit committee, the board of commissioners and tax aggressiveness to CSR disclosure with the object of research being companies listed in SRI KEHATI Index for the period 2009-2019. The sample have been selected using purposive sampling method and data analysis using multiple regression analysis. The results showed that profitability, audit committee, managerial ownership and tax aggressiveness partially had an influence on CSR disclosure. Meanwhile, solvency, company size, independent commissioners and institutional ownership no effect on CSR disclosure. The coefficient of determination shows a number of 0.164. This explains that the independent variables in this study are able to explain the CSR disclosure of 16.4% while the remaining 83.6% consists of other factors which are not discussed in this study.